The Dictatorship Game: Simulating a Transition to Democracy - Jiménez, Luis F. (PS, political science & politics, 2015)
A central topic in the comparative-politics subdiscipline is the study of democratic transitions. Despite a growing role-playing literature, there are currently no simulations that illustrate the dynamics of democratic transitions. This article proposes a role-playing simulation that demonstrates to students why it is difficult for countries to transition to democracy and why protests are a necessary but not sufficient condition to topple a dictatorship. As surveys and teaching evaluations subsequently showed, this exercise succeeded in clarifying the more difficult theoretical concepts as well as in making a potentially dry subject more accessible.